Eliminating race-based mental health disparities : promoting equity and culturally responsive care across settings - Williams, Monnica T.; Rosen, Daniel C.; Kanter, Jonathan; Arredondo, Patricia (Oakland, CA : Context Press, an imprint of New Harbinger Publications, Inc., 2019)
In this edited volume, three leading experts in race, mental health, and contextual behavior science address the urgent problem of racial inequities and biases, which often prevent people of color from seeking mental health services--leading to poor outcomes if and when they do receive treatment. This critical and timely guide provides clinicians and educators with evidence-based recommendations for addressing inequities at multiple levels, as well as best practices for compassionately and effectively helping clients across a range of cultural groups and settings.
Foreword : evidence-based practices and recommendations for clinicians and educators / Patricia Arredondo -- Acknowledgments -- Introduction / Monnica T. Williams, Daniel C. Rosen, Jonathan W. Kanter -- Understanding mental health disparities / Amanda NeMoyer, Kiara Alvarez, Margarita Algería -- Barriers to mental health treatment for African Americans : applying a model of treatment initiation to reduce disparities / Erlanger A. Turner, Celeste M. Malone, Courtland Douglas -- The science of clinician biases and (mis)behavior / John F. Dovidio, Ava T. Casados -- Strategies for promoting patient activation, self-efficacy, and engagement in treatment for ethnic and racial minority clients / Margarita Alegría, Naomi Ali, Larimar Fuentes -- The impact of racism on the mental health of people of color / Shawn C. T. Jones, Enrique W. Neblett Jr. -- Using contextual behavioral science to understand racism and bias / Jonathan W. Kanter, Daniel C. Rosen, Katherine E. Manbeck, Adam M. Kuczynski, Mariah D. Corey, Heather M. L. Branstetter -- Cultural competence 101 : teaching about race and racism / Monnica T. Williams -- Becoming an antiracist white clinician / Daniel C. Rosen, Jonathan W. Kanter, Matthieu Villatte, Matthew D. Skinta, Mary Plummer Loudon -- Culturally responsive assessment and diagnosis for clients of color / Jessica R. Graham-LoPresti, Monnica T. Williams, Daniel C. Rosen -- Supervising therapist trainees of color / Linda A. Oshin, Terence H. W. Ching, Lindsey M. West -- White parents raising black kids / Anne Blakely Steketee -- Strategies for increased racial diversity and inclusion in graduate psychology programs / Erin N. Arney, Sharon Y. Lee, Destiny M. B. Printz, Catherine E. Stewart, Sylvie P. Shuttleworth -- Promoting diversity and inclusion on college campuses / Monnica T. Williams, Jonathan W. Kanter -- Barriers to outpatient psychotherapy treatment / Camelia Harb, Jessica Jackson, Alfiee M. Breland-Noble -- Racial disparities in university counseling centers / M. R. Natacha Foo Kune, Agnes Kwong, Ellen B. Taylor -- Mental health treatment disparities in racial and ethnic minority military service members and veterans / Elizabeth M. Goetter, Allyson M. Blackburn -- Refugee communities / Victoria A. Schlaudt, Alisa B. Miller.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 11, 2019).
eBooks on EBSCOhost
Keywords: African Americans -- Mental health services; African Americans -- Mental health; Discrimination in mental health services -- United States -- Prevention; Health and race -- United States; Mental health services; Black or African American -- psychology; Mental Health Services; Race Factors; Noirs américains -- Services de santé mentale; Noirs américains -- Santé mentale; Santé et race -- États-Unis.; Services de santé mentale; Psychiatry; MEDICAL; Social Psychology; PSYCHOLOGY; Discrimination & Race Relations; SOCIAL SCIENCE; Mental health services; African Americans -- Mental health; African Americans -- Mental health services; Health and race; United States